How amateur golfers deliver energy to the driver - MacKenzie, S.; McCourt, M.; Champoux, L. (International Journal of Golf Science, 2020)
The work the golfer does on the club is the primary determinant of clubhead speed and is a function of four factors: hand path length, average force along the hand path, club angular distance, and the average couple applied over this distance. The primary purpose was to evaluate the relative importance of these factors in generating clubhead speed. The drives of 76 golfers were captured using a launch monitor and an optical system. Regression was used to determine the relative importance of each of the four factors. Average force accounted for the greatest proportion of variability in clubhead speed (r = .96). Hand path length (r = .45) and the average golfer applied couple (r = .45) were also found to be meaningful predictors of clubhead speed, while angular distance was not (r = .14). These findings will be applicable to instructors and golfers attempting to increase clubhead speed.